New Mining Concessions Could Severely Decrease Biodiversity and Ecosystem Services in Ecuador. (June 2018) - Roy, Bitty A.; Zorrilla, Martin; Endara, Lorena; Thomas, Dan C.; Vandegrift, Roo; Rubenstein, Jesse M.; Policha, Tobias; Ríos-Touma, Blanca; Read, Morley
Ecuador has among the world's highest biodiversity, despite being a tiny fraction of the world's land area. The threat of extinction for some of this biodiversity has dramatically increased since April 2016, during which time the Ecuadorian government has opened around 13% of the country to mining exploration, with many of the concessions in previously protected forests . Herein, we describe the system of protected lands in Ecuador, their mining laws, and outline the scale of threat by comparing the mammals, amphibians, reptiles, birds, and orchids from several now threatened protected areas, classed as "Bosques Protectores, " in the northwestern montane cloud forests. Together, these reserves form a buffer and a southern corridor for the still-protected Cotacachi-Cayapas Ecological Reserve, which is otherwise now surrounded by mining concessions. We gathered published literature, "gray literature, " information from reserve records and websites, and our previously unpublished observations to make comparative species tables for each reserve. Our results reveal the potential losses that mining could cause: eight critically endangered species, including two primates (brown-headed spider monkey and white-fronted capuchin), 37 endangered species, 153 vulnerable, 89 near threatened, and a large number of less threatened species. Our data show that each reserve protects a unique subset of taxa in this region of highly localized endemics and the reserves also generate sustainable income for local people. The short-term national profits from mining will not compensate for the permanent biodiversity losses, and the long-term ecosystem service and economic losses at the local and regional level.